Report on Reliability Enhancement of Aircraft Engine Control System Using Sensor Modelling and Redundancy Management Techniques - SHAHERIAZ (2008)
INTERNAL GUIDE: R M O GEMSON MVJCE EXTERNAL GUIDE: A N VISHWANATH RAO ECSG GTRE
Keywords: Report on Reliability Enhancement of Aircraft Engine Control System Using Sensor Modelling and Redundancy Management Techniques